Investigating the effects of customer-based brand equity on turnover intentions with mediating effect of customer citizenship behavior - Raza, Mohsin; Salleh, Salniza; Tariq, Beenish; Altayyar, Raed Saud; Shaari, Hasnizam (Growing Science Ltd., 2020)
This study addresses the issue of rising turnover intention in Pakistan’s aviation industry and provides a theoretical foundation for lowering the turnover intention with the help of consumer citizenship behavior (CCB) and consumer-based brand equity by using the S-O-R theory. The data is collected with the help of structured personally administered questions following the intercept approach. Three most frequently used international airports which are located at Lahore, Karachi and Peshawar are targeted for data collection and total of 388 Pakistani flyers who traveled to international destinations participate in the survey. In addition, this study uses SmartPLS 3.2.7 for data analysis with the help of a two-stage approach. The results state that CBBE had a significant effect on CCB and CCB had a significant impact on turnover intentions. Furthermore, CCB plays the role of an important mediator for the effect of customer based brand equity (CBBE) on turnover intention. These results enhance existing literature about lowering the turnover intention with the help of CCB and CBBE in aviation industry of Pakistan. The study also highlights that managers and practitioners should improve customer engagement for exhibiting CCB to reduce customer turnover intentions in the aviation industry.